2021
DOI: 10.1002/cbf.3680
|View full text |Cite
|
Sign up to set email alerts
|

The role of fatty acid amide hydrolase enzyme inhibitors in Alzheimer's disease

Abstract: Fatty acid amide hydrolase (FAAH) is a prominent enzyme of the endocannabinoid system that degrades endogenous cannabinoid anandamide and oleamide. These lipid amides are involved in reducing neuroinflammation, pain and regulation of other neurological‐related activities including feeding behaviours, sleep patterns, body temperature, memory processes and locomotory activity. Many of these activities are affected in most neurological disorders. Increased levels of brain FAAH expressions are speculated to correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 103 publications
(176 reference statements)
0
12
0
Order By: Relevance
“…Nahuoic acid A (29), oleamide (37), erucamide (52), oligomycin C (78), and plakevulin A (101) are known as inhibitors of different enzymes [52][53][54][55]. Some of identified compounds (17,18,34,37,41,59, and 111) are characterized by anti-inflammatory or antimalarial properties [42,43,49,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Nahuoic acid A (29), oleamide (37), erucamide (52), oligomycin C (78), and plakevulin A (101) are known as inhibitors of different enzymes [52][53][54][55]. Some of identified compounds (17,18,34,37,41,59, and 111) are characterized by anti-inflammatory or antimalarial properties [42,43,49,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…As seen in the docking picture A1 is showing 1 hydrogen bonding (Dark green line) and 4 hydrophobic (pink line) interactions with the protein along with 7 carbonhydrogen bond (light green lines) and 1 pi-anion interaction (orange lines). The amino acids in common are Gly 181, Agr 215, Val 28, Glu 32, Lys 514, and Pro 29 [19][20][21][22][23].…”
Section: Dockingmentioning
confidence: 99%
“…The title compound was obtained as a white solid with a 99% yield; mp 162−164 °C. N-(Adamantan-1-yl)-4-hydroxybenzamide (18). The title compound was obtained as a white solid with a 76% yield; mp 220−222 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In 2003, Benito and colleagues found high expression of CB2R and Fatty Acid Amide Hydrolase (FAAH), the enzyme responsible for the degradation of the main endocannabinoid anandamide and related signaling lipids, in neuritic plaque-associated glia in the brains of AD patients, suggesting a potential involvement of these two targets in neurodegeneration . Thus, pharmacological action on these two targets could be particularly advantageous to contrast inflammatory processes because raised concentrations of anandamide also induce a reduction in the levels of pro-inflammatory cytokines, reactive oxygen species (ROS), and prostaglandins as a result of the activation of non-canonical endocannabinoid receptors such as the vanilloid receptor TRPV1 and peroxisome proliferator-activated receptors (PPARs) . Notably, it has been demonstrated that the therapeutic effects of FAAH inhibitors often come free of the psychotropic side effects typical of phytocannabinoids, and FAAH inhibitors have proven to be generally safe, provided that they are non-covalent and that they are not indiscriminate inhibitors of brain serine hydrolases. , The activation of CB2R is likewise unrelated to psychotropic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation